High-dose omeprazole infusion compared with scheduled second-look endoscopy for prevention of peptic ulcer rebleeding: a randomized controlled trial - Chiu, Philip Wai Yan; Joeng, Henry Kin Ming; Choi, Catherine Lai Yin; Tsoi, Kelvin Kam Fai; Kwong, Kwok Hung; Lam, Siu Ho; Sung, Joseph Jao Yiu (Endoscopy, 2016)
Background and study aim: Previous studies have shown that both scheduled second-look endoscopy and high-dose continuous omeprazole infusion are effective in preventing peptic ulcer rebleeding. The aim of this noninferiority trial was to compare the efficacy of these two strategies for the prevention of rebleeding following primary endoscopic hemostasis.Patients and methods: Consecutive patients who received endoscopic treatment for bleeding peptic ulcers (actively bleeding, with nonbleeding visible vessels) were randomized to two treatment groups following hemostasis. One group (second-look endoscopy group) received the proton pump inhibitor (PPI) omeprazole as an intravenous bolus every 12 hours for 72 hours and a second endoscopy within 16 – 24 hours with retreatment for persistent stigmata of bleeding. The other group (PPI infusion group) received continuous high-dose omeprazole infusion for 72 hours. Patients who developed rebleeding underwent surgery if repeat endoscopic therapy failed. The primary outcome was the rebleeding rate within 30 days after initial hemostasis. The margin for noninferiority was set at 5 %.Results: A total of 153 patients were randomized to the PPI infusion group and 152 to the second-look endoscopy group. Rebleeding occurred within 30 days in 10 patients (6.5 %) in the PPI infusion group and in 12 patients (7.9 %) in the second-look endoscopy group (P = 0.646). Surgery was required for rebleeding in six patients from the PPI infusion group and three patients in the second-look endoscopy group (P = 0.32). Intensive care unit stay, transfusion requirements, and mortality were not different between the groups. Patients in the second-look endoscopy group were discharged 1 day earlier than those in the PPI infusion group (P < 0.001).Conclusions: After endoscopic hemostasis, high-dose PPI infusion was not inferior to second-look endoscopy with bolus PPI in preventing peptic ulcer rebleeding.Trial registration: ClinicalTrials.gov (NCT: 00164931).